Real-time forecasting for monetary policy analysis: The case of Sveriges Riksbank - Jens Iversen; Stefan Laséen; Henrik Lundvall; Ulf Söderström (Sveriges Riksbank, 2016)
We evaluate forecasts made in real time to support monetary policy decisions at Sveriges Riksbank (the central bank of Sweden) from 2007 to 2013. We compare forecasts made with a DSGE model and a BVAR model with judgemental forecasts published by the Riksbank, and we evaluate the usefulness of conditioning information for the model-based forecasts. We also study the perceived usefulness of model forecasts for central bank policymakers when producing the judgemental forecasts.
Keywords: E37; E52; 330; Real-time forecasting; Forecast evaluation; Monetary policy; Inflation targeting